CPRecycle: Recycling Cyclic Prefix for Versatile Interference Mitigation in OFDM based Wireless Systems - Rathinakumar, Saravana; Marina, Mahesh K.; Radunovic, Bozidar (Conext, 2016)
OFDM is currently the most popular PHY-layer carrier modulation technique, used in the latest generations of cellular, Wi-Fi and TV standards. OFDM systems use cycle prefix to mitigate inter-symbol interference. However, most of the existing systems over-provision the size of the cycle prefix considering the worst case scenarios which rarely occur. We propose a novel OFDM PHY receiver design, called CPRecycle , that exploits the redundant cycle prefix to reduce the effects of interference from neighboring nodes. CPRecycle is based on the key observation that the starting position of the FFT window within the cyclic prefix at the OFDM receiver does not affect the received signal but can substantially reduce interference from concurrent transmissions. We further develop an algorithm that is able to find the optimal starting position of the FFT window for each subcarrier using a Gaussian kernel density function and a fixed sphere maximum likelihood detector. Through implementation and extensive evaluations using USRP and offthe-shelf IEEE 802.11g transmitters/interferers, we show the effectiveness of CPRecycle in significantly mitigating interference. CPRecycle only requires local modifications at the receiver and does not require changes in standards, making it incrementally deployable.